English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

answers:
x^2-15x+3
x^2-15x-3
x^2+15x+3
x2+15x-3

2007-02-12 05:36:25 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

x^2+10x-(-5x+3)
=x^2+10x+5x-3
=X^2+15x-3

2007-02-12 05:42:37 · answer #1 · answered by dla68 4 · 0 0

Subtract

x^2 + 15x -3

2007-02-12 13:40:22 · answer #2 · answered by richardwptljc 6 · 0 0

f(x)=x^2+10x and g(x)=-5x+3

(f-g)(x) = f(x) - g(x) = (x^2+10x) - (-5x+3)
= x^2+10x + 5x - 3
= x2+15x-3

2007-02-12 13:47:31 · answer #3 · answered by simbionte 2 · 0 0

fedest.com, questions and answers